2017
DOI: 10.1126/scisignal.aal4186
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β promotes PI3K-AKT signaling and prostate cancer cell migration through the TRAF6-mediated ubiquitylation of p85α

Abstract: Transforming growth factor-β (TGF-β) is a pluripotent cytokine that regulates cell fate and plasticity in normal tissues and tumors. The multifunctional cellular responses evoked by TGF-β are mediated by the canonical SMAD pathway and by noncanonical pathways, including mitogen-activated protein kinase (MAPK) pathways and the phosphatidylinositol 3'-kinase (PI3K)-protein kinase B (AKT) pathway. We found that TGF-β activated PI3K in a manner dependent on the activity of the E3 ubiquitin ligase tumor necrosis fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 62 publications
6
143
0
Order By: Relevance
“…Hamidi A also suggests that TGF‐b nay activate the PI3K signaling pathway, promote the migration of tumor cells. The correlation between TGF‐b and the PI3K signaling pathway was observed by former studies . Apart from that, Boguslawska et al demonstrate that TGF‐b, COL1A1, and THBS2 expression in gastric cancer cells are related to the survival time of gastric cancer patients, which suggests that COL1A1 and THBS2 may influence the activation of the PI3K signaling pathway by upregulating the TGF‐b.…”
Section: Discussionmentioning
confidence: 82%
“…Hamidi A also suggests that TGF‐b nay activate the PI3K signaling pathway, promote the migration of tumor cells. The correlation between TGF‐b and the PI3K signaling pathway was observed by former studies . Apart from that, Boguslawska et al demonstrate that TGF‐b, COL1A1, and THBS2 expression in gastric cancer cells are related to the survival time of gastric cancer patients, which suggests that COL1A1 and THBS2 may influence the activation of the PI3K signaling pathway by upregulating the TGF‐b.…”
Section: Discussionmentioning
confidence: 82%
“…As TGFβ activates Akt and induces the expression of CIN85 [49,50,86], these data suggest that recycling of TGFβ receptors can be regulated via a positive feedback loop, where TGFβ stimulation promotes the transport of the TGFβ receptors to the cell surface.…”
Section: Recyclingmentioning
confidence: 95%
“…2). It has been also shown that Smad7 is required for the TGFβ-induced activation of the phosphatidylinositol 3′-kinase (PI3K)-protein kinase B (Akt) pathway [49,50]. It is not known, however, whether receptor signaling complexes containing Smad7 are located in caveolae in these cases.…”
Section: Distribution Of Tgfβ Receptors In the Plasma Membranementioning
confidence: 95%
“…Men et al 25 demonstrated that TNXB mapped in pathways of focal adhesion, ECM receptor interaction, and calcium signaling pathway. Sanchez‐Antolín et al 37 previously reported that TNXB affected the activation of the TGF‐β signaling, and TGF‐β could interact with the PI3K‐Akt signaling, potentially 38 . Since the exact role or mechanism of TNXB in ESCC remained largely undiscovered, here, we conducted co‐expression and gene set enrichment analysis using mRNA expression data in ESCC.…”
Section: Discussionmentioning
confidence: 99%